Intertextual Irony of Post-9/11 American Social Structure in Mean Girls (2004) by Mark Waters: English - Syahrevi Khairani; Yoga Sudarisman; Irdan Hildansyah (Journal of English Development, 2025)
This research explores how the movie Mean Girls (2004) reflects the social structure of post-9/11 America using intertextual irony and stereotypes. Following the 9/11 attacks, American society experienced significant cultural and social shifts that influenced various media, including movies. This study analyzes how the film critiques social hierarchies and collective trauma while examining power dynamics and identity struggles in the context of high school as a microcosm of broader social tensions. The study employs a qualitative descriptive method with a literary sociology approach. The analysis draws on Julia Kristeva's intertextuality theory and Stuart Hall's stereotype theory to examine the interplay between the film's narrative elements and the sociocultural changes after 9/11. Primary data includes scenes and dialogues from the film, while secondary data comprises academic articles and news reports discussing the societal impacts of the tragedy. The findings reveal that the film employs intertextual irony to critique social exclusivity, power struggles, and the reinforcement of stereotypes. It also highlights the pressures of conformity and the challenges faced by marginalized identities. The study underscores the role of media in reflecting societal tensions and facilitating critical discourse on historical and cultural transformations. This research contributes to the academic understanding of popular culture by demonstrating how films like Mean Girls serve as both entertainment and a medium for social critique, particularly in addressing adolescent behavior and social dynamics within a historical context.